2016
DOI: 10.1177/0269216316635881
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care for HIV-infected patients with malignancies: A questionnaire-based survey

Abstract: Our findings suggest that in Japan, HIV patients with malignancies have difficulties obtaining hospitalization at a palliative care unit, which is likely due to a lack of experience among the professionals in treating such patients as well as a lack of knowledge about HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…[ 56 58 ] Despite this shift, there remains a low rate of palliation and hospice care for HIV patients, highlighting a need for improved end-of-life support in this population. [ 59 ] The same trend of more deaths in hospitals has been reported in a similar study that suggests that the higher rate of hospital deaths in HIV cases may stem from communication challenges and disenfranchisement reported by MSM as well as the need to initiate or modify ART for which the hospitals provide the infrastructure and expertise. [ 60 ]…”
Section: Discussionmentioning
confidence: 60%
“…[ 56 58 ] Despite this shift, there remains a low rate of palliation and hospice care for HIV patients, highlighting a need for improved end-of-life support in this population. [ 59 ] The same trend of more deaths in hospitals has been reported in a similar study that suggests that the higher rate of hospital deaths in HIV cases may stem from communication challenges and disenfranchisement reported by MSM as well as the need to initiate or modify ART for which the hospitals provide the infrastructure and expertise. [ 60 ]…”
Section: Discussionmentioning
confidence: 60%
“…As such, this would cause the professionals’ lower likelihood of providing hospice care services for advanced HIV patients. A previous nationwide hospital survey in Japan showed that 11.2% of healthcare providers at palliative care units were not willing to provide EOL care for PLWH due to lack of knowledge and experience in treating advanced HIV patients nearing death 21. Since hospice and palliative care services are associated with improvements in quality of life among patients towards the EOL,7 it is important to provide hospice care service for PLWH during EOL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Timely referral of patients with hepatic failure pertain to recent/recurrent hepatic severe decompensation and not being a candidate for liver transplant [41]. The human immunodeficiency virus (HIV) disease, despite much longer prognosis when properly treated, encompasses acquired immunodeficiency syndrome (AIDS), cases not responding to antiretroviral therapy and with the co-existence of malignancies or dementia [42].…”
Section: Prognosis-based Criteriamentioning
confidence: 99%